Asthma in Sickle Cell Disease - Manisha Newaskar; Karen A. Hardy; Claudia R. Morris (The Scientific World Journal)
In recent years, evidence has increased that asthma predisposes to complications of sickle cell disease (SCD), such as pain crises, acute chest syndrome, pulmonary hypertension, and stroke, and is associated with increased mortality. An obstructive pattern of pulmonary function, along with a higher-than-expected prevalence of airway hyper-responsiveness (AHR) when compared to the general population, has led some researchers to suspect that underlying hemolysis may contribute to the development of a pulmonary disease similar to asthma in patients with SCD. While the pathophysiologic mechanism in atopic asthma involves up-regulation of Th2 cytokines, mast cell– and eosinophil-driven inflammation, plus increased activity of inducible nitric oxide synthase (iNOS) and arginase in airway epithelium resulting in obstructive changes and AHR, the exact mechanisms of AHR, obstructive and restrictive lung disease in SCD is unclear. It is known that SCD is associated with a proinflammatory state and an enhanced inflammatory response is seen during vaso-occlusive events (VOE). Hemolysis-driven acute-on-chronic inflammation and dysregulated arginines–nitric oxide metabolism are potential mechanisms by which pulmonary dysfunction could occur in patients with SCD. In patients with a genetic predisposition of atopic asthma, these changes are probably more severe and result in increased susceptibility to sickle cell complications. Early recognition and aggressive management of asthma based on established National Institutes of Health asthma guidelines is recommended in order to minimize morbidity and mortality.